Енеолітичні поховання Північно-Західного Приазов’я - Рассамакін, Ю.Я. (Археологія, 1990)
Останнім часом Запорізькою експедицією ІА АН УPCP розкопано два кургани з енеолітичними похованнями, що містили важливі матеріали для визначення культурної належності, періодизації та відносної хронології найдавніших курганів степової України. На основании новых материалов автором выделяются особенности погребального ритуала и конструкции курганов эпохи энеолита. Сравнительный анализ новых памятников позволяет выделять пять обрядовых групп погребений и рассматривать их в рамках азово-черноморской линии развития степного энеолита. Стратиграфия курганов указывает на возможность выделения двух этапов развития последней: первый — до появления нижнего слоя Михайловского поселения, второй, последующий, до появления позднеямных памятников. New data permit the author to distinguish peculiarities of the burial ceremony and construction of Eneolitic burial mounds. Comparative analysis of new monuments makes it possible to single out five ceremonial groups of burials and to consider them within the frames of the Azov-Black Sea line in the development of the steppe Eneolithic. Stratigraphy of the burial mounds allow distinguishing two stages in the development of this line, the first — to the appearance of the lower layer of the Mikhailovskoe settlement, the second and subsequent — to the appearance of the Late-Yam monuments.